Third Strategy in Tissue Engineering: Tissue Spheroids Encaged into Microscaffolds - Rezende, Rodrigo A. (2016)
Tissue engineering is a biomedical technology of artificial development of living three-dimensional human tissues and organs. Tissue engineering is based on two distinct premises. First more conventional approach uses solid biodegradable porous scaffolds as a temporal supporting framework for living cells attachment and sequential formation of three-dimensional tissue whereas second emerging approach is a solid scaffold-free directed tissue self-assembly with using tissue spheroids or microtissues as building blocks. In this paper novel hybrid approach or so-called third strategy in tissue engineering which combines advantages of first and second approaches is presented. The novel concept of lockyballs or tissue spheroids encaged into interlockable synthetic microscaffolds is described.